A facies of Kophobelemnon (Cnidaria, Octocorallia) from Santa Maria di Leuca coral province (Mediterranean Sea). (18th April 2013) - Mastrototaro, Francesco; Maiorano, Porzia; Vertino, Agostina; Battista, Daniela; Indennidate, Antonella; Savini, Alessandra; Tursi, Angelo; D'Onghia, Gianfranco
Abstract During a research cruise carried out in April 2010, aimed at updating the knowledge on the biodiversity of the Santa Maria di Leuca (SML) cold‐water coral province (Mediterranean Sea), a facies of the sea pen Kophobelemnon stelliferum (Muller, 1776) was found on mud‐dominated bottoms. This finding represents a new species and a new habitat record from the SML coral province as well as a new bathyal facies in the whole Central Mediterranean Sea. The colonies were collected using an epi‐benthic sledge, at depths between 400 and 470 m. A significant positive relationship between polyp number and colony length was detected. Density of the colonies ranged from 0.003 to 0.038 N·m−2. Differences and affinities between Mediterranean and Atlantic occurrences of K. stelliferum are discussed.